(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2013)
Electricity is a critical input for all kinds of economicactivities like industrial, agriculture, and commercial and has a vital role toplay in economic development and wealth generation for a country. It is alsoused as a source of light, heat and air-conditioning and as the motive force inthe modern household appliances, thereby dramatically improving the quality oflife. Electricity also has an overall positive impact on education, health andthe environment – in reducing both emission and the pressure on forests.Lighting alone could not provide an economical market for electricity becauseits use was confined to the hours of darkness. Successful commercial generationdepended upon the development of other uses for electricity and particularly onelectric traction. There are number of studies covering the working of theState Electricity Board’s and their role in the economic development of aneconomy. Hence an attempt is made by the researcher to examine the performanceof Dakshin Haryana Bijli Vitran Nigam Limited in the present paper.